2022
DOI: 10.1039/d1nr90265b
|View full text |Cite
|
Sign up to set email alerts
|

Correction: A mesoporous polydopamine nanoparticle enables highly efficient manganese encapsulation for enhanced MRI-guided photothermal therapy

Abstract: Correction for ‘A mesoporous polydopamine nanoparticle enables highly efficient manganese encapsulation for enhanced MRI-guided photothermal therapy’ by Yan Wu et al., Nanoscale, 2021, 13, 6439–6446, DOI: D1NR00957E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Due to the doping of polydopamine, the nanoparticles have the characteristics of easy modification of silicon materials and have a particular photothermal version. It was reported that, temperature ≥40°C may have selective destruction effects on certain types of cancer cells 17 at 42°C, it has a demanding and irreversible inhibitory impact on the metabolism of various tumor cells while normal cells are unaffected (Figure 3(a) and (b)). After irradiation with a 2 W/cm 2 808 nm laser, the temperature can rise from 9°C to 40°C in 1200 s at a concentration of 125 μg/m and 62.5 μg/mL, the stability of the photothermal effect of the particles was tested In the five cycles within 6000 s, the time required for the nanoparticle to cycle five times from 32°C to 49°C is between 440 s and 480 s, in the presence of low concentration of nanoparticles, it still has an excellent photothermal cycling ability (Figure 3(c)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the doping of polydopamine, the nanoparticles have the characteristics of easy modification of silicon materials and have a particular photothermal version. It was reported that, temperature ≥40°C may have selective destruction effects on certain types of cancer cells 17 at 42°C, it has a demanding and irreversible inhibitory impact on the metabolism of various tumor cells while normal cells are unaffected (Figure 3(a) and (b)). After irradiation with a 2 W/cm 2 808 nm laser, the temperature can rise from 9°C to 40°C in 1200 s at a concentration of 125 μg/m and 62.5 μg/mL, the stability of the photothermal effect of the particles was tested In the five cycles within 6000 s, the time required for the nanoparticle to cycle five times from 32°C to 49°C is between 440 s and 480 s, in the presence of low concentration of nanoparticles, it still has an excellent photothermal cycling ability (Figure 3(c)).…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13] It is often used as an additive to boost materials' photothermal effect. Therefore, it is considered that the addition of PDA can exert excellent photothermal effect and acid degradability while possessing the high specific surface area, [14][15][16][17] tuneable size and modifiability of MSN.…”
Section: Introductionmentioning
confidence: 99%